Buya Hamka Character Values in forming Pancasila Student Profiles in Elementary - Pradini, Nadia Putri Liani; Nugroho, Arya Setya (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The application of the Pancasila Student Profile in elementary schools experiences difficulties if it is not linked to real evidence from everyday life or figures. This research aims to determine the value of Buya Hamka’s character in forming Pancasila student profiles in elementary schools. The focus of the problem that will be studied by researchers is related to the many problems that occur among elementary schools, such as the decline in attitudes that exemplify Pancasila students. Strengthening character education is implemented in the process of realizing the Pancasila student profile and as an effort to shape students’ positive character. This research uses a qualitative literature review research design methodology. The results of this research show that the character of buya hamka corresponds to four of the six characteristics of the Pancasila student profile, namely faith and devotion to God Almighty, mutual cooperation, critical thinking, and creativity. Buya Hamka’s character is relevant to forming the profile of Pancasila Students in